2019
DOI: 10.1152/jn.00004.2019
|View full text |Cite
|
Sign up to set email alerts
|

Single-motor-unit discharge characteristics in lumbar multifidus muscle of acute low back pain patients

Abstract: Acute low back pain (ALBP) causes rapid deterioration of paraspinal muscle function. The underlying neurophysiology is poorly understood. We therefore carried out this observational study in patients with ALBP to characterize motor unit (MU) activity in deep lumbar multifidus (LM) muscle and compare with our previous findings from pain-free subjects. Nine subjects (1 woman; age 26–59 yr) with ALBP duration of 1–21 days were recruited from outpatient clinics. Fine wire electromyography (EMG) electrodes were imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…Contradictory evidence was also reported in a recent study that investigated muscle tone using EMG. The study conducted by Lothe et al, [43] reported no significant difference in muscle activity between people with low back pain when compared to pain free participants. Other study provided evidence to support that people with low back pain have different muscle activation pattern among the synergy muscles groups [44].…”
Section: Discussionmentioning
confidence: 99%
“…Contradictory evidence was also reported in a recent study that investigated muscle tone using EMG. The study conducted by Lothe et al, [43] reported no significant difference in muscle activity between people with low back pain when compared to pain free participants. Other study provided evidence to support that people with low back pain have different muscle activation pattern among the synergy muscles groups [44].…”
Section: Discussionmentioning
confidence: 99%